THE CONTENT OF DEVELOPING SOCIO-CULTURAL COMPETENCE IN FUTURE TEACHERS (International Conference on Modern Science and Scientific Studies, 2025)
This article analyzes the content of the development of socio-cultural competence in future educators. During the study, the importance of harmonizing the basic principles, approaches, socio-cultural knowledge, skills and qualifications of 21st century education with national and international historical experiences in the organization of the educational process in students of higher educational institutions was studied. In future educators, the form, method, tools for the development of socio-cultural competence are analyzed theoretically and practically. In the activities of future educators, recommendations have been developed to improve the effectiveness of education by harmonizing values with modern methods